A Population-Level Summary of Health Care Utilization for the Management of Patellar Tendinopathy in the Military Health System - Young, Jodi L.; Schroeder, Jeremy D.; Westrick, Richard B.; Nowak, Matthew; Rhon, Daniel I. (The Journal of Knee Surgery, 2022)
Patellar tendinopathy (PT) is a common nontraumatic orthopaedic disorder of the knee suffered by many service members. Understanding the make-up of usual care for PT at the system level can better frame current clinical gaps and areas that need improvement. Exercise therapy is recommended as a core treatment for PT, but it is unclear how often it is used as a part of usual care for PT within the Military Health System (MHS). The purpose of the study was to identify interventions used in the management of PT and the timing of these interventions. A secondary purpose was to determine if exercise therapy use was associated with reduced recurrence of knee pain. In total, 4,719 individuals aged 17 to 50 years in the MHS diagnosed with PT between 2010 and 2011 were included. Pharmacological and nonpharmacological interventions, visits to specialty providers, and imaging services were captured. Descriptive statistics were used to report the findings. Interventions were further categorized as being part of initial care (within the first 7 days), the initial episode of care (within the first 60 days), or the 2-year time period after diagnosis. Linear regression assessed the relationship between the number of exercise therapy visits in the initial episode of care and recurrences of knee pain. In total, 50.6% of this cohort had no more than one medical visit total for PT. Exercise therapy (18.2%) and nonsteroidal anti-inflammatory drugs (4.3%) were the two most used interventions in the initial episode of care. Radiographs were ordered for 23.1% of the cohort in the initial episode of care. The number of exercise therapy visits a patient received during the initial episode of care was not associated with recurrences of knee pain. Half of the individuals received no further care beyond an initial visit for the diagnosis of PT. Exercise therapy was the most common intervention used during the initial episode of care, but exercise therapy did not influence the recurrence of knee pain.
Keywords: patellar tendinopathy; knee pain; exercise therapy